A fluorescent Arg–Gly–Asp (RGD) peptide–naphthalenediimide (NDI) conjugate for imaging integrin αvβ3in vitro. Issue 32 (3rd February 2015) - Hu, Zhiyuan; Arrowsmith, Rory L.; Tyson, James A.; Mirabello, Vincenzo; Ge, Haobo; Eggleston, Ian M.; Botchway, Stanley W.; Dan Pantos, G.; Pascu, Sofia I.
Abstract : We have developed a fluorescent peptide conjugate (TrpNDIRGDfK) based on the coupling of cyclo(RGDfK) to a new tryptophan-tagged amino acid naphthalenediimide (TrpNDI). Abstract : We have developed a fluorescent peptide conjugate (TrpNDIRGDfK) based on the coupling of cyclo(RGDfK) to a new tryptophan-tagged amino acid naphthalenediimide (TrpNDI). Confocal fluorescence microscopy coupled with fluorescence lifetime imaging (FLIM) mapping, single and two-photon fluorescence excitation, lifetime components and corresponding decay profiles were used as parameters able to investigate qualitatively the cellular behavior regarding the molecular environment and biolocalisation of TrpNDI and TrpNDI–RGDfK in cancer cells.